Enlightenment Ideals and Belief in Progress in the Run-up to the Industrial Revolution: A Textual Analysis - Ali Almelhem; Murat Iyigun; Austin Kennedy; Jared Rubin (Institute of Labor Economics (IZA), 2023)
Using textual analysis of 173,031 works printed in England between 1500 and 1900, we test whether British culture evolved to manifest a heightened belief in progress associated with science and industry. Our analysis yields three main findings. First, there was a separation in the language of science and religion beginning in the 17th century. Second, scientific volumes became more progress-oriented during the Enlightenment. Third, industrial works—especially those at the science-political economy nexus—were more progress-oriented beginning in the 17th century. It was therefore the more pragmatic, industrial works which reflected the cultural values cited as important for Britain's takeoff.
Keywords: C81; C88; N33; N63; O14; Z11; 330; language; religion; science; political economy; progressiveness; Enlightenment; industrial revolution